Climate Justice and the Law: Legal Mechanisms for Protecting Climate Refugees in the Global South - Lukas Müller; Marta Sánchez; Sofia Conti; Nabilah Ismail; Leila Ben Mansour (Artes Libres Institutum, 2025)
Climate-induced displacement is rapidly emerging as one of the most pressing humanitarian crises of our time, yet international legal frameworks remain ill-equipped to address the plight of climate refugees. This paper investigates the legal invisibility of climate-displaced persons within the 1951 Refugee Convention and other international human rights instruments. Through case studies in the Pacific Islands, Bangladesh, and Sub-Saharan Africa, the paper examines national and regional responses to environmentally induced migration and assesses their effectiveness in offering legal protection and human security. The novelty of this study lies in its focused legal analysis of climate displacement from the perspective of the Global South—an angle often marginalized in global legal discourse. Unlike existing literature that primarily offers normative arguments for reform, this paper systematically evaluates concrete legal gaps and proposes a rights-based framework grounded in environmental justice, international solidarity, and climate reparations. This research contributes to the expanding field of climate justice by reframing climate-induced migration as a legal and ethical issue of global inequality, rather than merely a humanitarian challenge. It critically engages with international debates surrounding state responsibility, climate finance, and the need for a new international treaty or legal recognition of climate refugee status. The paper concludes with policy recommendations that emphasize the urgency of integrating climate displacement into global migration governance, with an emphasis on legal dignity, human rights, and equitable burden-sharing.